2003
DOI: 10.1074/jbc.m305536200
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor (TLR) 2 and TLR5, but Not TLR4, Are Required for Helicobacter pylori-induced NF-κB Activation and Chemokine Expression by Epithelial Cells

Abstract: Infection with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
370
5
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(400 citation statements)
references
References 35 publications
20
370
5
5
Order By: Relevance
“…HCT116 cells do not express detectable amounts of TLR2 and TLR4. HEK293T cells also do not express detectable amounts of TLR4 and TLR2, consistent with previous reports (11,30). In contrast, HCT116 express both Nod1 and Nod2 mRNA.…”
Section: Methodssupporting
confidence: 79%
“…HCT116 cells do not express detectable amounts of TLR2 and TLR4. HEK293T cells also do not express detectable amounts of TLR4 and TLR2, consistent with previous reports (11,30). In contrast, HCT116 express both Nod1 and Nod2 mRNA.…”
Section: Methodssupporting
confidence: 79%
“…5B). It has been reported that intestinal epithelial cells do not respond to LPS due to their lack of expression of the TLR4 coreceptor MD4 (1,2,54). Consistent with these reports, incubation of T84 cells with 10 g/ml of purified E. coli LPS increased the IL-8 secretion level only slightly.…”
Section: Campylobacter Increases Il-8 Secretion In Polarized Human Insupporting
confidence: 80%
“…It may also be an evolutionarily acquired adaptive attribute of the mammary gland to help it fight infections since it is constantly under attack by invading pathogens. Furthermore, TLR2 has been shown to recognize LPS preparations from sources like Leptospira interrogans, Porphyromonas gingivalis, and Helicobacter pyroli, all non-enterobacteria [21,36,43]. Another study demonstrated TLR2/CD14 complex as the exogenous mediators of Trypanosoma cruzi induced inflammation [8].…”
Section: Discussionmentioning
confidence: 99%